Teachers’ dissatisfaction during the COVID-19 pandemic: Factors contributing to a desire to leave the profession - Gillani, Amreen; Dierst-Davies, Rhodri; Lee, Sarah; Robin, Leah; Li, Jingjing; Glover-Kudon, Rebecca; Baker, Kayilan; Whitton, Alaina (Frontiers in Psychology, 2022)
Introduction: The COVID-19 pandemic required more responsibilities from teachers, including implementing prevention strategies, changes in school policies, and managing their own mental health, which yielded higher dissatisfaction in the field. Methods: A cross-sectional web survey was conducted among educators to collect information on their experiences teaching during the COVID-19 pandemic throughout the 2020-2021 academic year. Qualtrics, an online survey platform, fielded the survey from May 6 to June 8, 2021 to a national, convenience sample of 1,807 respondents. Results: Findings revealed that overall, 43% of K-12 teachers reported a greater intention to leave the profession than previously recalled prior to the COVID-19 pandemic. Intention to leave was multi-level, and associated with socio-demographic factors (e.g., age: AOR=1.87, p<0.05), individual factors (e.g., perceived COVID risks: AOR=1.44, p<0.05)), and teachers’ agency (e.g., dissatisfaction with school/district communications and decisions: AOR=1.34, p<0.05). We also found demographic disparities with respect to race and gender (e.g., female teachers: AOR:1.78, p<0.05) around teachers’ ability to provide feedback to schools on opening/closing and overall dissatisfaction with school/district COVID-19 prevention strategies implementation and policies. Conclusion: These findings are consistent with the Job-Demand and Resources Model (JD-R), which posits that lack of organizational support can exacerbate job stressors, leading to burnout. Specifically, dissatisfaction with the way school policies were implemented took a toll on teachers’ mental health, leading to a desire to leave the profession. These findings are also consistent with research conducted once in-person teaching resumed in 2020-2021, specifically that the COVID-19 pandemic exacerbated preexisting teacher shortages that led to self-reported issues of stress, burnout, and retention. Implications: Further research is necessary to understand the resources that may be most useful to reduce the demands of teaching in the context of the COVID-19 pandemic. Some teachers are more likely to leave the field, and educational agencies may wish to target their teacher-retention efforts with emphasis on strong employee wellness programs that help educators to manage and reduce their stress. Education agency staff may wish to review policies and practices to provide meaningful opportunities to give input to school/district decisions and enable proactive communication channels.